Complete feed of corn silage and its effect on male Bali cattle performance, feed consumption, and beef quality - Syamsuddin Hasan; A. Mujnisa; Rinduwati Rinduwati; Sema Sema; Apiaty Kamaluddin; Fatmawati Annisa Syamsuddin; Purnama Isti Khaerani (Universitas Sebelas Maret, 2024)
Objective: This study aims to observe the effect of feeding corn silage combined with elephant grass and cheap concentrate feed on male Bali cattle performance, feed consumption, and beef quality. Methods: Animal feed testing was performed in male Bali cattle weighing 150-200 kg for 90 days, and the cattle were slaughtered in a slaughterhouse to observe the beef quality. This study employed a completely randomized design with 4 treatments and 3 replicates. Research treatment: The proportion of 30% corn silage + 60% elephant grass + 10% concentrate feed as A1; 50% corn silage + 40% elephant grass + 10% concentrate feed as A2; 70% corn silage + 20% elephant grass + 10% concentrate feed as A3; 100% corn silage as A4. The observed parameters in include average daily gain, dry matter consumption, organic matter consumption, crude protein consumption, total digestible nutrients, tenderness, beef color, water-holding capacity, cooking loss, and aroma. Results: The results showed that the treatments significantly affect the consumption of dry matter with the highest A4 is 2.44% of body weight, organic matter with the highest A3 is 8.43 kg/head/day, crude protein with the highest A3 is 0.82 kg/head/day, and total digestible nutrients with the highest A3 is 4.88 kg/head/day. There is a significant difference in daily average weight gain (ADG) from the three treatments (P<0.05).Conclusions: It can be concluded that A3 treatment, supplemented with 70% corn silage concentration, 20% elephant grass, and 10% concentrate feed is more effective in improving male Bali cattle performance, feed, consumption, and beef quality.